Pilot Testing a Brief Partner-Inclusive Hybrid Intervention for Perinatal Mood and Anxiety Disorders - Peifer, Janelle S.; Bradley, Erin; Taasoobshirazi, Gita (Frontiers in Psychiatry, 2022)
The necessity of hybrid and more accessible options for perinatal mood and anxiety disorders (PMADs) has taken on increased urgency in the wake of the COVID-19 pandemic and its lasting impacts. In the New Family Wellness Project (NFWP), participants engage in a hybrid in-person and teletherapy six-session intervention for new parents early in their postpartum period. This small, phase 1 clinical research examined early outcomes of the NFWP’s cognitive behavioral intervention on adverse mental health outcomes (i.e., perinatal depression and anxiety, overall mental illness symptoms) and adaptive outcomes and protective factors (i.e., relational health, social support, flourishing, self-efficacy). Despite a small sample size (N=12), paired t-tests yielded significant effects for improvements in mental health symptoms at posttest, as well as marginally significant improvements in postpartum anxiety and self-efficacy. Findings suggest the brief, partner-inclusive, hybrid intervention shows promise for further study. Lessons learned from this small phase 1 clinical study and recommendations for revising the intervention prior to future trials are discussed.